Respon Jambu Mete Bermikoriza terhadap Pengurangan Dosis Pupuk NPK - Usman Daras; Octivia Trisilawati; Enny Randriani (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The objective was to find out the response of mycorrhizal cashew to the decreasing doses of NPK fertilizer in the green house. Experiment was carried out in the green house of Cikampek research garden at Indonesian Spices and Industrial Crops Research Institute, and ecofisiology,s laboratory at Indonesian Medicinal and Aromatic Crops Research Institute, Bogor for 6 months. The research was arranged factorially, in completelly randomized design, with 2 factors, 8 combinations and 4 replications. The first factor was AMF inoculation : control and 300 spores of AMF/plant, and the second factor consisted of 4 rates of NPK fertilizer : full dose (8 g Urea, 8 g SP-36, and 6 g KCl per pot), 3/4 dose, 1/2 dose, and ¼ dose. The observation parameters were plant growth parameter, the uptake of N, P, K and chlorophyll content. The result indicated that AMF inoculation positively effected the growth variable of cashew. AMF significantly increased leaf dry weight (19,8%) compared to without AMF, besides it also increased the content of chlorophyll a, b and total chlorophyll at low level of NPK (1/4 and ½ doses of NPK). The uptake of NPK of mycorhizal cashew leaf increased about 43,8%, 53% and 49% compared to without AMF. The decreasing level of NPK to ½ NPK at mycorrhizal cashew (5 months after planting) resulted good performance of plant growth.